One-Voice Strategy for Customer Engagement. (February 2021) - Singh, Jagdip; Nambisan, Satish; Bridge, R. Gary; Brock, Jürgen Kai-Uwe
Machine-age technologies, including automation, robotics, and artificial intelligence, are profoundly expanding the variety of service interfaces and therefore the possible ways that customers and firms can interact across customer journeys. This expansion challenges service firms' capabilities to deliver coherent streams of interactions for effective customer engagement. This article develops a conceptual framework of firm capabilities that enable firms to operate with "one voice" to deliver seamless, harmonious, and reliable interactions across diverse interfaces in a customer journey. The proposed framework integrates three themes: (1) service interaction space to capture the interrelationship among devices, interfaces, interactions, and journeys; (2) learning and coordination as core capabilities for generating and using intelligence, respectively, to enhance customer engagement in subsequent interactions; and (3) one-voice strategy to configure learning and coordination capabilities in combinations that meet conditions of fitness and equifinality for effective customer engagement. We provide several research questions and priorities to guide research and practice.